2014
DOI: 10.1002/ptr.5168
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Effects and Chemical Constituents of Veronicastrum axillare

Abstract: Our study aims to ascertain the antiinflammatory activity of Veronicastrum axillare and characterize the bioactive constituents. Antiinflammatory activity of the total extract and different fractions from V. axillare was investigated by employing the xylene-induced mouse ear edema model. As a result, the ethyl acetate (EtOAc) fraction showed the highest antiinflammatory activity in vivo. From the EtOAc fraction and the inactive dichloromethane fraction, a total of five new compounds, axillasides A-C and axilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It is the major anti-inflammatory constituent of the EtOAc fraction of V. axillare . Interestingly, the anti-inflammatory effect of procumboside A seems to be stronger than that of dexamethasone which is also used as a positive drug in a previous study [7]. Nevertheless, the interactions among active compounds in the natural products are complex with potential synergistic/antagonistic effects, which attracts great interest in TCM research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the major anti-inflammatory constituent of the EtOAc fraction of V. axillare . Interestingly, the anti-inflammatory effect of procumboside A seems to be stronger than that of dexamethasone which is also used as a positive drug in a previous study [7]. Nevertheless, the interactions among active compounds in the natural products are complex with potential synergistic/antagonistic effects, which attracts great interest in TCM research.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work indicated that V. axillare significantly inhibits ethanol-induced gastric ulcers [6]. Recently, it was shown that the ethyl acetate (EtOAc) extracts of V. axillare displayed potent anti-inflammatory activity in vivo using xylene-induced mouse ear edema model [7]. Nevertheless, effects of V. axillare against ALI and potential anti-inflammatory mechanisms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Veronicastrum axillare (Sieb. et Zucc) Yamazaki (Scrophulariaceae) has been widely used both alone and in conjugation with other herbs in Chinese folk medicines to treat injuries from chronic nephritis, pleural effusion, gastric ulcer, furunculosis, burns, snake bites, and other ailments [ 8 – 13 ]. Our preliminary studies showed that the water extract of V. axillare significantly reduced ethanol-induced gastric damage in a rat model and downregulation of the expression of the key factors of NF- κ B signaling pathway [ 14 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this species is primarily found in the grasslands of the mountainous regions of southeastern China, it has also spread to Japan (Zheng et al. 2014 ). V. axillare has been used as a folk medicine named ‘Fushuicao’ to treat nephritic edema, cirrhotic ascites, venomous snakebite, and furuncles (Deng et al.…”
mentioning
confidence: 99%